Dependence evaluation of weather factors on crop capacity of winter crops in the northern part of Lugansk region - Зубов, О. Р.; Зубова, Л. Г.; Славгородська, Ю. В. (Scientific Progress & Innovations, 2012)
In the article the complex analysis of climate factors and productivity of agricultural landscapes is carried out at the typical agricultural enterprise in the north of Lugansk Region having taken as an example. Mathematical and statistical models of correlation dependence of crop capacity for winter crops upon weather factors for the 36-year period are defined as a result of the investigations. The most influential weather factors for winter wheat are determined to be the quantity of precipitation in June, September and May; for winter rye – the quantity of precipitation in June, September and April.